Value of the Cause in Labor Proceedings: Estimation or Limitation of Future Execution? (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the legal controversy regarding the indication of values in initial labor claims after Law No. 13,467/2017. The author discusses whether the values assigned in the complaint should serve only as an estimate for jurisdiction and court costs or if they limit the amount of the award in the execution phase. The conflict between procedural speed and the principle of full reparation is examined, defending that absolute liquidity is impractical without prior access to documents held by the employer. (Received: June 2025 | Accepted: September 2025).
Keywords: Value of the Cause; Labor Reform; Labor Execution.